An efficient composite magnetocaloric material with a tunable temperature transition in K-deficient manganites. Issue 41 (7th April 2016) - Skini, R.; Khlifi, M.; Hlil, E. K.
Abstract : This paper reports on a magnetic material with high steady relative cooling power (RCP) over a temperature range from 325 to 275 K induced by potassium-deficiency in polycrystalline samples of La0.8 K0.2− x □ x MnO3 ( x = 0, 0.1 and 0.2). Abstract : This paper reports on a magnetic material with high steady relative cooling power (RCP) over a temperature range from 325 to 275 K induced by potassium-deficiency in polycrystalline samples of La0.8 K0.2− x □ x MnO3 ( x = 0, 0.1 and 0.2). The possibility to adjust the temperature transition close to room temperature exists by changing the potassium deficiency rate. All the samples were synthesized using the citrate-gel method. X-ray diffraction and magnetization measurements were conducted to examine the crystallographic structure and magnetocaloric properties. All the samples were found to be a single phase and crystallize in rhombohedral symmetry with R 3̄ c space group. From the magnetic measurements, a second-order magnetic phase transition from the ferromagnetic to paramagnetic state was noticed at the Curie temperature ( T C ), which was found to decrease from 325 to 275 K when the potassium-deficiency rate increased. Besides, the magnetocaloric effect (MCE) as well as the RCP has been estimated. The obtained results have confirmed that our manganite with potassium-deficiency has significant advantages for magnetic refrigeration. Finally, the critical behavior associated with the magnetic phase transition reveals that the estimated critical exponents are consistent with the prediction of the mean field theory ( β = 0.5, γ = 1, and δ = 3) for the x = 0.00 and x = 0.10 samples, while the estimated critical exponents for x = 0.2 were consistent with the prediction of the 3D-Heisenberg model ( β = 0.365, γ = 1.336 and δ = 4.8).